2022
DOI: 10.1155/2022/5260131
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Sutureless in Partial Nephrectomy: A Systematic Review and Meta-Analysis

Abstract: Purpose. To compare the effect of sutureless versus standard suture (double-layer suture) during renorrhaphy in laparoscopic or robotic-assisted partial nephrectomy on perioperative and renal function outcomes. Methods. PubMed, Embase, and other sources were searched for randomized controlled trials or retrospective studies comparing sutureless partial nephrectomy versus standard suture partial nephrectomy. A systematic review and meta-analysis were performed by two reviewers independently. Results. Five retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Indeed, these results verify and add to data by other groups around the world investigating novel approaches to maximal renal function preservation. A meta-analysis assessing the literature for surgical outcomes when attempting sutureless PN by Liu and colleagues showed that using this approach had a smaller decline in eGFR, no signi cant difference in post-operative complications, shorter operative time and warm ischemia time, and no signi cant blood loss difference or rates of urine leak when compared to SR. (15) The meta-analysis included both robotic and laparoscopic studies but was reassuring as the outcomes assessed are some of the rst concerns that come to mind when considering the use of a sutureless approach.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these results verify and add to data by other groups around the world investigating novel approaches to maximal renal function preservation. A meta-analysis assessing the literature for surgical outcomes when attempting sutureless PN by Liu and colleagues showed that using this approach had a smaller decline in eGFR, no signi cant difference in post-operative complications, shorter operative time and warm ischemia time, and no signi cant blood loss difference or rates of urine leak when compared to SR. (15) The meta-analysis included both robotic and laparoscopic studies but was reassuring as the outcomes assessed are some of the rst concerns that come to mind when considering the use of a sutureless approach.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, bipolar and monopolar coagulation minimize intraoperative bleeding by coagulating tissue and sealing blood vessels. The thulium laser, precise and minimally damaging, is ideal for delicate kidney resections, while argon beam coagulation effectively coagulates larger bleeding areas [5][6][7][8][9][10]. These technologies reduce WIT, crucial for protecting renal function, especially in small T1a tumors, and can shorten surgical time and reduce blood loss, improving safety and effectiveness [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The stable conversion rates observed in our study also indirectly emphasize the low learning threshold of the sutureless technique, which seems to be unrelated to the surgeon's experience. This may be due to the intuitive operation process and fewer steps involved in the sutureless technique, thereby reducing the time and experience required to learn and master it [9,10]. Moreover, the simpli cation of the technique might also reduce the reliance on advanced skills of surgeons, allowing even less experienced surgeons to perform the surgery safely and effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A newer renorrhaphy technique, which involves the use of sliding clips instead of knots, has offered quicker renal suturing, a reduced learning curve, and a decrease in the "cheese-cutting effect" [104]. The common contemporary renorrhaphy technique typically consists of two tiers of suturing: a deeper layer at the excision site and a shallower layer [96,101,[105][106][107][108][109][110]. However, in the case of larger defects, achieving complete reapproximation of the capsule may be challenging, particularly when dealing with hilar renal masses to prevent compression of the renal hilum [111][112][113].…”
Section: Suturing Techniques For Renal Hilar Massesmentioning
confidence: 99%